Pengembangan Modul Bimbingan Karir tentang Perencanaan Karir Siswa - Yurike Kinanthy Karamoy; Haris Nur Afif; Fakhruddin Mutakin (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2023)
ABSTRACT: This research aims to develop a media in guidance and counseling services in the form of a module on career planning to produce a module that is suitable for use for students of class X SMA Argopuro. This study uses Borg and Gall development research up to stage 5. The development procedures are: 1) needs analysis, 2) planning, 3) developing the initial product, 4) testing the initial product, and 5) revising the initial product. Based on the results of the validation test of the career guidance module on career planning, the results of the material expert assessment obtained a percentage of 85.00% in the excellent category, the results of the media expert assessment obtained a percentage of 85.00% in the excellent category, the results of the media expert assessment obtained a percentage of 92 .50% in the excellent category, and the results of the BK service expert's assessment obtained a percentage of 92.50% in the excellent category. The average score is 88.75 so it is included in the very good category and has been revised into the final product (draft 2). Thus, it can be concluded that the research product in the form of a career guidance module on career planning is declared content-worthy and can be used by BK teachers to provide an understanding of student career planning at the high school level.